Phosphorylation of the Hepatitis B Virus Large Envelope Protein - Fogeron, Marie-Laure; Lecoq, Lauriane; Cole, Laura; Montserret, Roland; David, Guillaume; Page, Adeline; Delolme, Frédéric; Nassal, Michael; Böckmann, Anja (Frontiers in Molecular Biosciences, 2022)
We here establish the phosphorylation sites in the human hepatitis B virus (HBV) large envelope protein (L). L is involved in several functionally important interactions in the viral life cycle, including with the HBV cellular receptor, HBV capsid, Hsc70 chaperone, and cellular membranes during fusion. We have recently shown that cell-free synthesis of the homologous L protein of duck HBV in wheat germ extract results in very similar phosphorylation events to those previously observed in animal cells. Here, we used mass spectrometry and NMR to establish the phosphorylation patterns of human HBV L protein produced by both in vitro cell-free synthesis and in E. coli with the co-expression of the human MAPK14 kinase. While in the avian virus the phosphorylation of L has been shown to be dispensable for infectivity, the identified locations in the human virus protein, both in the PreS1 and PreS2 domains, raise the intriguing possibility that they might play a functional role, since they are found at strategic sites predicted to be involved in L interactions. This would warrant the further investigation of a possible function in virion formation or cell entry.